المنهج الدعوي في الحوار النبويﷺ ودروسه الدعوية مع ذكر بعض النماذج من الصحيحين: The Method of Preaching Derived From the Dialogue of the Prophetﷺ - Siddique, Dr. Tahir (Al Basirah, 2022)
Dialogue has been always a very effective way of communication amongst human beings and communities. The Holy Prophets have been traditionally using the same, as the source and means to preach God’s message. The Holy Prophet Muhammad (PBUH) had been extraordinary and matchless in this regard as well. The following study focuses on lessons from the Holy Prophet’s Dialogues as an Analytic Derivative Study (selected Aḥadīth from Bukhāri and Muslim) to learn how The Holy Prophet (PBUH) communicated in various roles as an individual, such as orator, leader, husband, merchant, president of the state, preacher, and as a family member. The analysis will derive etiquette for preaching from the Sīrah of the Holy Prophet (PBUH).